Fostering Interdisciplinary Research Culture, Challenges and Way Forward: The Universiti Malaya Experience - Abdul-Rahman, Puteri Shafinaz; Abdul Rahim, Haryana Rozana; Osman, Normaniza (Journal of Research Management and Governance, 2021)
Interdisciplinary research (IDR) exploring beyond the purview of a single discipline is critical for providing the requisite solutions to real-world issues. Furthermore, the process of translating research that could have a positive impact on and benefit the government, industry and society, typically requires a multipronged approach with inputs and solutions integrated from various disciplines. Therefore, IDR is vital in pushing the different disciplines forward and accelerating scientific discovery in innovative ways. Nonetheless, the move towards encouraging researchers to break away from working in silos to working together has been an extremely challenging task. Doubtlessly, interdisciplinary programmes demand much more involvement and exhaustive effort from researchers per se as they require not only academic scholarship but also soft skills to communicate, network and engage with other researchers from diversified disciplines, various stakeholders and beneficiaries. In addition to that, good leadership and all-rounded teamwork support are required in navigating and ensuring the success of the research programme to deliver its intended outcome and impact. In light of this, this opinion paper discusses some of the challenges confronted in fostering IDR at the Universiti Malaya and suggestions on approaches that could be adopted to garner the interest and move it forward.